A systematic literature review exploring the prevalence of post-traumatic stress disorder and the role played by stress and traumatic stress in breast cancer diagnosis and trajectory - Arnaboldi, Paola (Breast Cancer (Dove Med Press), 2017)
Stress has been extensively studied as a psychosomatic factor associated with breast cancer. This study aims to review the prevalence of post-traumatic stress disorder (PTSD), its associated risk factors, the role of predicting factors for its early diagnosis/prevention, the implications for co-treatment, and the potential links by which stress could impact cancer risk, by closely examining the literature on breast cancer survivors. The authors systematically reviewed studies published from 2002 to 2016 pertaining to PTSD, breast cancer and PTSD, and breast cancer and stress. The prevalence of PTSD varies between 0% and 32.3% mainly as regards the disease phase, the stage of disease, and the instruments adopted to detect prevalence. Higher percentages were observed when the Clinician Administered PTSD Scale was administered. In regard to PTSD-associated risk factors, no consensus has been reached to date; younger age, geographic provenance with higher prevalence in the Middle East, and the presence of previous cancer diagnosis in the family or relational background emerged as the only variables that were unanimously found to be associated with higher PTSD prevalence. Type C personality can be considered a risk factor, together with low social support. In light of the impact of PTSD on cognitive, social, work-related, and physical functioning, co-treatment of cancer and PTSD is warranted and a multidisciplinary perspective including specific training for health care professionals in communication and relational issues with PTSD patients is mandatory. However, even though a significant correlation was found between stressful life events and breast cancer incidence, an unequivocal implication of distress in breast cancer is hard to demonstrate. For the future, overcoming the methodological heterogeneity represents one main focus. Efficacy studies could help when evaluating the effect of co-treating breast cancer and post-traumatic stress symptoms, even if all the criteria for a Diagnostic and Statistical Manual of Mental Disorders diagnosis are not fulfilled.